Merging Fargesia dracocephala into Fargesia decurvata (Bambusoideae, Poaceae): Implications from Morphological and ITS Sequence Analyses - Zhang, Yu-Qu (Public Library of Science, 2014)
AIMS: Fargesia decurvata is closely allied with F. dracocephala and differs in 5 major characters (i.e. the culm sheath blade base shape, the width of the culm sheath blade base, the auricle shape, and the lower surface of leaf blade) in Fargesia. It is difficult to distinguish these two species because of existing of transitional statements of characters. The aims of this paper are to (i) investigate whether the variation of the characters is continuous or not; (ii) reveal whether the publishment of F. dracocephala was the result of discontinuous sampling of F. decurvata or not. METHODS: Ten populations of F. decurvata and F. dracocephala were investigated in their entire distribution (including type localities). The statements of 5 major characters were measured from 693 annual and 693 perennial culms of 231 individuals in 10 populations, and analyzed at population, individual and culm levels. UPGMA cluster analysis was carried out based on 29 characters from 10 populations of F. decurvata and F. dracocephala and 2 populations of F. qinlingensis as outgroup. The ITS sequences were also sequenced and analyzed. IMPORTANT FINDINGS: Five major characters exhibited great variation not only at population level, but at individual level within a population, even the culm level within an individual and in different parts of the same culm. Cluster analyses showed that 10 populations of F. decurvata and F. dracocephala were not divided into two species, but they were well separated with outgroup. There was no difference in floral organ between F. decurvata and F. dracocephala. MP and NJ trees based on ITS sequences showed the same results with the cluster analysis on morphological characters. All the facts indicated that the publishment of F. dracocephala was the result of discontinuous sampling of F. decurvata, and F. dracocephala should be treated as the synonym of F. decurvata.